2018
DOI: 10.1590/1678-7757-2017-0449
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology and mechanical properties of conventional and self-adhesive resin cements after aqueous aging

Abstract: The stable long-term performance of resin cement under oral environmental conditions is a crucial factor to obtain a satisfactory success of the allceramic dental restoration. Objective: This study aimed at evaluating and comparing the surface morphology and mechanical property of conventional and self-adhesive resin cement after aqueous aging. Materials and Methods: Disc-shaped specimens of 3 conventional (C1: Multilink N, C2: Duolink, C3: Nexus 3) and 3 self-adhesive (S1: Multilink Speed, S2: Biscem, S3: Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
(29 reference statements)
0
21
0
1
Order By: Relevance
“…3 An important aspect to consider is that the resin cement film around the margins of the restorations is often located close to the free gingival margin or gingival sulcus, [4][5][6] a susceptible area of sorption, hydrolysis, and dynamic fatigue which may lead to polymer degradation. 7 Resin-based luting cement is methacrylate monomers with small filler contents and a photoinitiator. 5,6 In general, dental polymers' networks are not chemically stable and water impermeable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 An important aspect to consider is that the resin cement film around the margins of the restorations is often located close to the free gingival margin or gingival sulcus, [4][5][6] a susceptible area of sorption, hydrolysis, and dynamic fatigue which may lead to polymer degradation. 7 Resin-based luting cement is methacrylate monomers with small filler contents and a photoinitiator. 5,6 In general, dental polymers' networks are not chemically stable and water impermeable.…”
Section: Introductionmentioning
confidence: 99%
“…These monomers have been shown to absorb moisture, which is a critical property due to the adverse effects on hydrolytic stability. 8 This phenomenon may result in material discoloration, mechanical deterioration, degradation of filler-matrix interface, polymer swelling, weakening of the polymer network, 7,8 and stress-induced degradation of the resin cement leading to debonding or fracture of the ceramic restoration. 5,8 Many factors can influence the coefficient of water diffusion between the polymer network, including filler content and the resin matrix volume.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies shown RU, ME, and MS without light irradiation have lower polymerization degree or hardness than them with light irradiation [14][15][16][17][18], plus their high values of water absorption, solubility, and water expansion stress [6][7][8][9][10], which might lead to a series of changes in extract solution of self-adhesive resin cements. In this study, more distinct absorption peaks and higher absorption peak value occurred in the extract solution of each self-adhesive resin cement without light irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of the acidic monomers in the selfadhesive resin cements should be sufficiently high to achieve an acceptable bonding to the dentin and enamel; meanwhile, as the acid functionality is consumed through reaction with calcium on the tooth and a variety of metal oxides from the ion-leachable filler, these materials become more hydrophobic [3]. However, studies have indicated that most selfadhesive resin cements exhibited higher sorption and solubility than conventional resin cements [6][7][8][9][10]. The excessive hydrophilic character of self-adhesive resin cement can cause swelling that in turn can compromise surface dimensional stability [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation